2016
DOI: 10.1371/journal.ppat.1005401
|View full text |Cite
|
Sign up to set email alerts
|

Differential Toxicity of Antibodies to the Prion Protein

Abstract: Antibodies against the prion protein PrPC can antagonize prion replication and neuroinvasion, and therefore hold promise as possible therapeutics against prion diseases. However, the safety profile of such antibodies is controversial. It was originally reported that the monoclonal antibody D13 exhibits strong target-related toxicity, yet a subsequent study contradicted these findings. We have reported that several antibodies against certain epitopes of PrPC, including antibody POM1, are profoundly neurotoxic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 40 publications
3
90
0
Order By: Relevance
“…Judging by the additional interactions, the b2-a2 loop in moPrP:POM6 Fab appears more stable than the one in moPrP:POM1 Fab. It should also be noted, that similar orientations for this loop to that of the POM1 Fab bound moPrP have been observed in the PDB structure of the ICSM18 Fab bound with the human prion protein [35] which seems to cause dose dependent neurotoxicity [36]. Furthermore, the regions of the C-terminal part of helix a3 near to the b2-a2 loop in the moPrP:POM1 Fab has an angular shift of 9.6 degrees compared to the Cterrminus of the moPrP in the moPrP:POM6 Fab complex without any significant changes through the crystal contacts (Fig.…”
Section: Structural Comparisons Of Moprp:pom6 Fab and Moprp:pom1 Fabsupporting
confidence: 56%
“…Judging by the additional interactions, the b2-a2 loop in moPrP:POM6 Fab appears more stable than the one in moPrP:POM1 Fab. It should also be noted, that similar orientations for this loop to that of the POM1 Fab bound moPrP have been observed in the PDB structure of the ICSM18 Fab bound with the human prion protein [35] which seems to cause dose dependent neurotoxicity [36]. Furthermore, the regions of the C-terminal part of helix a3 near to the b2-a2 loop in the moPrP:POM1 Fab has an angular shift of 9.6 degrees compared to the Cterrminus of the moPrP in the moPrP:POM6 Fab complex without any significant changes through the crystal contacts (Fig.…”
Section: Structural Comparisons Of Moprp:pom6 Fab and Moprp:pom1 Fabsupporting
confidence: 56%
“…The surface of the PrP globular domain involved in the Cu 2+ -promoted cis interaction observed here overlaps the binding epitopes of several PrP C -specific antibodies that cause acute neurotoxicity (Reimann et al, 2016; Sonati et al, 2013). Sonati et al reported rapid neurotoxicity in mice and cultured cerebellar brain slices with antibody-based ligands that target specific regions of the PrP C globular domain (Sonati et al, 2013).…”
Section: Discussionmentioning
confidence: 63%
“…Antibodies that bind to the FT have been demonstrated to be neuroprotective, whereas those directed against certain epitopes of the GD are invariably toxic 11,21 . We therefore asked whether Fabs against CC123-50 (Fab3 and Fab83), the OR51-91 (Fab8, Fab44, Fab71 and Fab100) and the GD (Fab25, Fab1 and Fab29) may counteract neurotoxicity in prion-infected cerebellar slices (COCS) 11,22 .…”
Section: Activity Of Fabs In Models Of Prion Diseasementioning
confidence: 99%